Development of Integrated Thematic Textbooks Based on Picture and Picture Models at MIS Lubuk Karya, Dharmasraya - Rahmadani; Ayu Mustika Sari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by learning that is carried out at home by doing practice questions only in the student book. According to the researcher, the book still needs to be developed using the Picture and Picture learning model. In addition, learning at home is carried out independently without being accompanied by learning media that attracts students' attention. This study aims to describe the process of developing integrated thematic teaching materials based on the Picture and Picture model in grade IV SD that are valid, practical, and effective. This research was conducted at MIS Lubuk Karya. This type of research is development research. This study uses a 4-D model consisting of 4 stages, namely: define, design, develop, and disseminate stages. Validity test data were obtained through validation sheets of teaching materials, implementation of lesson plans, assessment of teacher and student responses. Effectiveness is seen from the activities, process assessment and student skill outcomes. Based on the research results, it is known that the teaching based on the picture and picture model has been valid based on the validity test by the validator. The teaching materials have been practical based on the results of the practicality test according to the responses of teachers and students. Teaching materials are said to be effective in terms of learning activities and improving learning outcomes. Thus, it can be concluded that the integrated thematic teaching materials based on the Picture and Picture model in grade IV SD have been declared valid, practical, and effective. It is hoped that teaching materials using the Picture and Picture model in thematic learning on other materials get more perfect results.